Students’ perception on Islamic education toward e-learning classes during covid-19 pandemic - Dewi Suriyani Djamdjuri; Maeleni Maeleni (ATTARBIYAH: Journal of Islamic Culture and Education, 2021)
The aim of this research is to find out the students’ perception of Islamic education course conducted online learning during a pandemic outbreak. This impact affects the learning process. The researchers used a qualitative research approach with a survey method and the data collection were gained through a questionnaire and interview which were conducted online. The participants in this study were 115 students from the even semester and of English Education Program in English for Islamic studies course from one of universities in Bogor, Indonesia, who had been involved in online learning during the Covid-19 pandemic. The results show that a hundred percent of the students of that program involved in online learning in 2020/2021 academic year. Moreover, the online media that students are most interested in when learning online are WhatsApp (40.3 %), Google Classroom (35.7 %), Telegram (12.4 %) and Zoom (4.4 %). In addition, according to the students’ perception if online learning was extended, some students were very happy, a number of students were unhappy, and a few students were less happy. Despite the fact that most students prefer to study in person (offline) at home, online learning has positive impact on students.